LITERATURE REVIEW: INTEGRATING SUSTAINABILITY AND DIGITAL INNOVATION IN WATERWAY TRANSPORT AND MARITIME LOGISTICS - Ugrinov, Stefan; Ćoćkalo, Dragan; Bakator, Mihalj; Stanisavljev, Sanja (Journal of Applied Engineering Science, 2025)
Modern waterway transport and maritime logistics industries are being transformed through sustainable practices combined with digital innovation which leads to better operational efficiency along with decreased environmental effects. Green technology adoption requires support from regulatory frameworks and financial incentives to meet emission reduction standards and promote investments in alternative fuels and energy-efficient solutions. IoT-enabled cargo tracking alongside blockchain supply chain transparency and AI predictive maintenance systems improve operational dependability through better resource management. Sustainable practices, including energy-efficient vessel design, route optimization, and shore power integration, contribute to lower fuel consumption and emissions. Smart ports and automated terminals streamline cargo handling, reducing energy use and improving supply chain efficiency. This study examines the relationship between regulatory policies, digital enablers, and sustainability strategies, demonstrating their collective impact on creating a more efficient and environmentally responsible maritime sector. This systematic review examines the intersection of sustainability and digital innovation in waterway transport and maritime logistics. Studies were sourced from Scopus, Web of Science, IEEE Xplore, ScienceDirect, and JSTOR, covering literature on supply chain efficiency, green technology, maritime logistics, inland waterway transport and digital transformation. A total of 52 studies met the inclusion criteria, focusing on regulatory policies, blockchain-enabled transparency, AI-driven predictive maintenance, and sustainable maritime and inland waterway operations. Findings highlight that digitalization enhances environmental sustainability while improving logistical efficiency. Future research should explore policy frameworks that encourage eco-digital maritime ecosystems. This study adheres to PRISMA 2020 guidelines to ensure transparency and rigor.